2000
DOI: 10.1046/j.1365-2443.2000.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

The conserved nuclear receptor Ftz‐F1 is required for embryogenesis, moulting and reproduction in Caenorhabditis elegans

Abstract: Background: Nuclear receptors are essential players in the development of all metazoans. The nematode Caenorhabditis elegans possesses more than 200 putative nuclear receptor genes, several times more than the number known in any other organism. Very few of these transcription factors are conserved with components of the steroid response pathways in vertebrates and arthropods. Ftz-F1, one of the evolutionarily oldest nuclear receptor types, is required for steroidogenesis and sexual differentiation in mice and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 65 publications
(59 reference statements)
6
91
1
Order By: Relevance
“…Interestingly, inhibition of nhr-23, nhr-25, and lrp-1 gene expression also resulted in some morphological abnormalities. All these genes, including cpz-1, are highly expressed in the major hypodermal cells in all larval stages of nematodes, which supports their involvement in epidermal differentiation during or after molting (45,46,48).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, inhibition of nhr-23, nhr-25, and lrp-1 gene expression also resulted in some morphological abnormalities. All these genes, including cpz-1, are highly expressed in the major hypodermal cells in all larval stages of nematodes, which supports their involvement in epidermal differentiation during or after molting (45,46,48).…”
Section: Discussionmentioning
confidence: 60%
“…Control mechanisms that regulate such a complicated process are poorly understood, but recent studies have implicated two C. elegans nuclear hormone receptors (NHR-23 and NHR-25) in the regulation of molting (45)(46)(47). Molting defects were observed after interference with C. elegans nhr-25 gene expression by RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…The nhr-25 gene encodes an orphan nuclear receptor in C. elegans, and loss of function by using microinjection of dsRNA into adult hermaphrodites results in progeny with molting and other defects (17,18). The Drosophila homologue of nhr-25 is ␤FTZ-F1.…”
Section: Gene Expression In Chr3 (Nhr-23) Rnaimentioning
confidence: 99%
“…Of the 270 C. elegans NHRs, only 15 are obvious orthologs of the NHRs of vertebrates or Drosophila; the rest of the C. elegans NHRs are probably nematode-specific. Studies of several of the C. elegans NHRs demonstrated a role for these factors in larval development [daf-12 (12)], neural development [nhr-55 (13) and fax-1 (14)], sex determination [nhr-24͞sex-1 (15)], and molting [nhr-23 (CHR3) (16) and nhr-25 (17,18)]. …”
mentioning
confidence: 99%
“…So far, the regulatory mechanisms of C. elegans molting are not yet understood, although about a dozen genes have been identified that lead to molting defects when mutated. These genes can be classified into five categories based on their possible functions: (1) proteases that are used to degrade the old cuticle, including a cathepsin Z-like cysteine protease (Cecpz-1) (Hashmi et al, 2004), and two metalloproteases, nas-36 and nas-37 (Davis et al, 2004;Suzuki et al, 2004); (2) transcriptional regulators, including nhr-23 (Kostrouchova et al, 1998(Kostrouchova et al, , 2001, nhr-25 (Asahina et al, 2000;Gissendanner and Sluder, 2000), and let-19 (Wang et al, 2004); (3) enzymes involved in cholesterol metabolism such as let-767 (Kuervers et al, 2003) or cholesterol transporters such as lrp-1 (Yochem et al, 1999); (4) molecules involved in secretion and extracellular transport such as sec-23 (Roberts et al, 2003) and CeVps-27 (Roudier et al, 2005); (5) others, such as the angiotensin converting enzyme-like non-peptidase acn-1 (Brooks et al, 2003).…”
Section: Introductionmentioning
confidence: 99%